Theoretical analysis of the S2←S0 vibronic spectrum of the 2-pyridone dimer - Kopec, Sabine; Köppel, Horst (The journal of chemical physics, 2016)
The interplay between excitonic and vibronic coupling in hydrogen-bonded molecular dimers leads to complex spectral structures and other intriguing phenomena such as a quenching of the excitonic energy splitting. We recently extended our analysis from that of the quenching mechanism to the theoretical investigation of the complete vibronic spectrum for the ortho-cyanophenol dimer. We now apply the same approach to the vibronic spectrum of the 2-pyridone dimer and discuss the assignment of vibronic lines to gain insight into the underlying coupling mechanism. This is based on potential energy surfaces obtained at the RI-CC2/aug-cc-pVTZ level. They are used for the dynamical analysis in the framework of a multi-mode vibronic coupling approach. The theoretical results based on the quadratic vibronic coupling model are found to be in good agreement with the experimental resonant two-photon ionization spectrum.
Gesehen am 14.05.2020